The clinicopathological profile and treatment outcomes of stage IV lung cancer patients treated at a tertiary cancer center in India - Shrivastav, Gunjan; Batra, Sandeep; Rohatgi, Nitesh; Gupta, Alok; Siddiqui, Hiba; Arya, Devavrat; Bahl, Ankur; Chaturvedi, Harit (International Journal of Research in Medical Sciences, 2024)
Background: Non-small cell lung cancer (NSCLC) is a devastating disease that originates from a complex combination of genetic, environmental, and lifestyle factors. A prospective study was conducted at Max Hospital, Saket, New Delhi, to assess the above factors in stage IV lung cancer patients and determine the survival rate and quality of life (QOL) parameters post-administration of the recommended first-line therapy. Methods: The primary objective of the study was to determine progression-free survival (PFS) in stage IV lung cancer patients after receiving the first-line therapy. This study also evaluated the clinical and histopathological profile of patients, survival rate, and QOL parameters after the administration of first-line therapy, which includes chemotherapy, tyrosine kinase inhibitors (TKI), immunotherapy, and chemo-immunotherapy. Results: The study enrolled 85 patients (63 males, 22 females) with a mean age of 64.08±10.3 years. The median PFS was 10.56 months, with a six-month survival rate of 74.3% and a one-year overall survival rate of 58.3%. Among stage IV lung cancer patients, adenocarcinoma was more common (64.71%), especially in females (86.36%) compared to males (57.14%). Out of 85 patients, 54 completed the QOL questionnaire at baseline and follow-up, showing significant improvement in QOL scores during follow-up (p<0.0001). Conclusions: This prospective study showed improvement in PFS compared to the studies already conducted in different parts of India. A notable trend of increase in NSCLC was observed among females. Improvement in QOL scores was observed in patients who received chemotherapy and TKI as the first-line therapy.